Decoupled Anisotropic Solutions Using Karmarkar Condition in f(G, T) Gravity - Komal Hassan; Muhammad Sharif (Universe, 2023)
In this paper, we compute two anisotropic static spherical solutions for two compact stellar candidates in the background of <semantics>f(G,T)</semantics> gravity using the minimal geometric decoupling technique. The internal structure becomes anisotropic when an additional sector is added to the isotropic system. With this method, the radial component is distorted to establish two sets of the field equations that represent perfect and anisotropic sources. We use the Karmarkar condition to formulate the metric potentials that help to find the solution of the first set. For the second set, two extra constraints are applied on theanisotropic sector to find its solution. Both of the solutions are then combined to yield the ultimate anisotropic solution. We then examine the physical feasibility and stability of the resulting anisotropic solutions through energy conditions and stability criteria, respectively. It is found that the compact star Her X-1 is viable but not stable corresponding to the first solution while satisfying all the physical acceptability conditions for the second solution. On the other hand, the star 4U 1820-30 indicates viable and stable behavior for both anisotropic solutions.